The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s13027-015-0040-y
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus genotypes among women with or without HIV infection: an epidemiological study of Moroccan women from the Souss area

Abstract: BackgroundData on Human PapillomaVirus (HPV) infection are scarce in Morocco. The objective of the study was to determine the prevalence of HPV and cervical cytology abnormalities in women from the Souss area, Morocco.MethodsTwo hundred and thirty two women who attended the Hassan II hospital (Agadir, Morocco) were recruited in this study. Socio-economic data, sexual activity, reproductive life, history of Pap smear, smoking and HIV status were recorded. Cervical samples were taken using an Ayre spatula. Cytol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
2
11
2
Order By: Relevance
“…The current study demonstrated the high HPV/HIV co-infection of 24.4%, with high hr-HPV prevalence across almost all age groups and more multiple hr-HPV infection in HIV-positive women than compared to HIV-negative women. These findings are consistent with previous studies reporting higher prevalence of HPV [9, 27, 30, 35] and higher frequency of infection with multiple HPV types among HIV infected women [30, 32, 36]. A number of risk factors for HPV infection among women have been demonstrated in previous studies, including having more than one partner, early sexual initiation, age and marital status.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study demonstrated the high HPV/HIV co-infection of 24.4%, with high hr-HPV prevalence across almost all age groups and more multiple hr-HPV infection in HIV-positive women than compared to HIV-negative women. These findings are consistent with previous studies reporting higher prevalence of HPV [9, 27, 30, 35] and higher frequency of infection with multiple HPV types among HIV infected women [30, 32, 36]. A number of risk factors for HPV infection among women have been demonstrated in previous studies, including having more than one partner, early sexual initiation, age and marital status.…”
Section: Discussionsupporting
confidence: 92%
“…According to Winer and colleagues, the actual first peak of HPV infection might be before the age of 25 years, as women are usually infected after sexual initiation [29]. HPV16 and 18 types have been found to be the most prevalent high risk types in most studies [4, 2628, 3032], yet in the current study we were not able to establish that. However, we observed high frequency of hr-HPV31/33/35/52/58 group types among the study population.…”
Section: Discussioncontrasting
confidence: 66%
“…That study and ours identified most of the known LR‐HPVs and the following HPV genotypes that are not classified as HR or LR; HPV 44, 32, 74, 85, 86, 102 and 97. HPV 44 and 74 have been previously detected in cervical specimens of HIV+ women . Additionally, we identified HPV 114 in our study which was previously reported in the cervix of HIV+ women …”
Section: Discussionsupporting
confidence: 73%
“…In addition, high HPV infection prevalence in HIV-positive women has been reported in Italy (44%) [30], US (54%-73%) [31], Brazil (48-78.8%) [32][33][34][35], South Africa (52.4%-74%) [36,37], Tanzania (54.1%) [27]and Burkina Faso (66.1%) [38]. However, a preliminary study carried out among 87 HIV-positive women in the Souss region (South of Morocco) reported a prevalence (39.3%) less than observed in our study [39].…”
Section: Discussioncontrasting
confidence: 47%